MAKER CULTURE AND MATHEMATICS CLUB – A SUCCESSFUL EXPERIENCE IN THE CLASSROOM - Ney de Lima dos Santos, Nora; Santos Medina, Cecília (Journal of Interdisciplinary Debates, 2024)
Introduction: The science of Mathematics, one of the oldest areas of knowledge, has the philosophy of bringing together abstract and concrete knowledge to build new know-how. This science studies numbers, magnitudes, shapes and possibilities, and maker culture emerges as a notable instrument for the student to establish the inseparable connection between theory and practice. Justification: maker culture is linked to constructivism despite learning by doing. The student learns with creativity, in teaching, in execution, in the art of continuing to learn throughout his life. The center of teaching-learning is the student who stars and writes his or her own story. Therefore, the implementation of the mathematics club in the public school was essential for achieving the objective: central to this study, which is to analyze the results of the implementation of a mathematics club through maker culture, in a state school with high school students. Medium in the second half of 2023. Methodology: The action project, mathematics club, focused on active methodologies, through maker culture (method). Entitled: maker culture and mathematics club – A pedagogical possibility for teaching and learning mathematics in high school, was developed within classrooms. Its methodology focused on observation and execution of different stages and with a qualitative focus it was possible to work on Results: more than numbers. Observation of the project, the experience as a teacher, resulted in theoretical-methodological gains and the students were able to develop a taste for learning Mathematics. Conclusion: With the Mathematics Club, maker culture can be shown as a pedagogical possibility for teaching and learning mathematics. All activities that focus on active methods allow for interactive and collaborative learning, especially with the use of digital technologies.